Peran Pemimpin dalam Pengambilan Keputusan pada Situasi Krisis - Regina Reni; Sandra Ligia Sari; Furkan Furkan; Abdurahman Abdurahman; Jelang Ramadhani; Irwan Irwan; Astriani Astriani (Journal of Research and Development on Public Policy, 2026)
This study aims to analyze the role of leaders in decision-making during crisis situations using the bounded rationality approach. The study is motivated by the fact that crises are often characterized by limited information, time constraints, and high levels of uncertainty, making fully rational decision-making difficult. This research employed a literature review method by examining relevant academic sources, including books, journal articles, and scholarly publications on leadership, decision-making, and bounded rationality. The findings indicate that leaders are often unable to make optimal decisions due to limitations in cognitive capacity, access to information, and dynamic environmental conditions. Under such circumstances, the bounded rationality model enables leaders to make satisfactory (*satisficing*) decisions that are practical and feasible to implement. This approach effectively reflects the realities of decision-making in crisis situations, where timely and appropriate responses are more critical than achieving optimal outcomes. Therefore, leaders are expected to demonstrate adaptability, strategic thinking, and the ability to evaluate risks and available resources to ensure effective decision-making. Applying bounded rationality can help organizations maintain stability, resilience, and operational continuity despite the challenges posed by crisis situations.